An Exploration of Dual Identity in Gene Luen Yang's 'American Born Chinese’ - Putra, Jonathan Syah; Sharenlie, Grania; Djohan, Febrina Stevani; Surya, Michaella Isabel; Supriadi, Ben Othniel; Wijaya, Josh Fitzkioshi; Nathanael, Jeshua (Jurnal Pendidikan Makarios, 2024)
This study aims at investigating the challenges of being a double minority and the impact of societal expectations on their sense of self in Gene Luen Yang's graphic novel, "American Born Chinese," exploring the themes of identity, racism, and discrimination prevalent within the narrative. Distinguishing novels from graphic novels, the study emphasizes the unique storytelling method of graphic novels, utilizing pictures with dialogue bubbles to convey complex and specific stories. The discussion centers on the novel's three interconnected stories featuring a monkey deity, Jin Wang, a Chinese boy facing bullying, and an American authentically Chinese individual named Jin Wang, addresses the issue of racism, particularly focusing on the superiority of white society and the stereotypes associated with the Chinese in American society, the Post-colonialism theory by Robert J. C. Young (2001) was used in the analysis. As a result: 1) Racism as the Central Theme: The racism is the central and overarching theme of the graphic novel. It explores how the narrative effectively portrays instances of racial discrimination and stereotypes, particularly focusing on the superiority of white supremacy and the negative perceptions associated with the Chinese in American society. 2) Impact on Identity: it shows the profound impact of racism on identity, emphasizing the challenges faced by the characters, especially Jin Wang, as a double minority; the struggles of being an American-born Chinese with a different belief system (Confucianism) and 3) It eventually shows the character’s identity reconstruction rather than a manifestation of identity crisis. The narrative encourages readers to reflect on the negative impact of racism, discrimination, and the importance of embracing one's true identity. Ultimately, the analysis serves as both an educational tool and a critique of societal issues, promoting empathy and understanding in the face of adversity.